Construction of a core collection and SNP fingerprinting database for Chinese chive (Allium tuberosum) through Hyper-seq based population genetic analysis - Zhang, Huamin; Li, Yanlong; Li, Taotao; Yan, Fangfang; Fu, Taotao; Liao, Chunli; Liu, Dongxiao; Zhu, Yutao; Zhao, Mei; Ma, Peifang; Wang, Lianzhe (Frontiers in Plant Science, 2025)
Chinese chive (Allium tuberosum Rottler ex Sprengel), an autotetraploid vegetable cultivated in Asia for over 3,000 years, possesses apomictic characteristics. However, issues like intricate genetic admixture and unclear phylogenetic relationships pose challenges for effective germplasm preservation and breeding advancements. In this research, we systematically assessed population structure, constructed a core collection, and developed a DNA fingerprinting system utilizing Hyper-seq sequencing data. Our Hyper-seq-based genotyping revealed 291,547 single nucleotide polymorphisms (SNPs) and 116,223 insertions/deletions (InDels). Population genetic analysis indicated that the 100 A. tuberosum accessions can be categorized into two distinct genetic subgroups. These subgroups partially aligned with previously recognized phenotypic classifications based on dormancy traits, underscoring the complex relationship between genetic divergence and adaptive phenotypic variation. A core collection consisting of 22 accessions (22% of the total) was created, maintaining 90.17% of the original genetic diversity. Additionally, we established a DNA fingerprinting system for all 100 accessions using 14 diagnostic SNP markers. This study marks the first comprehensive integration of SNP and InDel markers in systematic analysis of A. tuberosum genetic diversity, offering valuable resources for germplasm identification and marker-assisted breeding. These findings deepen the understanding of the genetic architecture of A. tuberosum and lay the foundation for molecularly driven breeding strategies.